Mutational profile in circulating tumor DNA in a patient affected by low-risk endometrial cancer: predictable tool of relapse?. Issue 10 (November 2020) - Malentacchi, Francesca; Turrini, Irene; Zepponi, Francesca; Fantappiè, Giulia; Sorbi, Flavia; Antonuzzo, Lorenzo; Fambrini, Massimiliano; Noci, Ivo; Pillozzi, Serena
Abstract : Endometrial cancer is the commonest gynecological cancer, the majority is endometrioid type, diagnosed at an early stage with 69–88% 5-year survival. Low-grade endometrial cancers have low recurrence rates and often do not receive adjuvant therapy; however, a subset of these patients will have poor outcomes and would benefit from adjuvant treatment has been challenging. We evaluate the circulating cell-free DNA (ccfDNA) in a patient with low-risk endometrial cancer in order to identify the presence of molecular markers associated with risk of recurrence. The evaluation of mutation profile was performed by next-generation sequencing (NGS) in primary tumor formalin-fixed paraffin-embedded (FFPE) tissue and in circulating tumor DNA (ctDNA). We identified a specific mutational profile in ctDNA, different from primary tumor tissue suggesting that the clone involved in the relapse may be different in comparison to the most represented in the primary tumor. These findings open new prospective and new wonderings. The molecular characterization of tissue may be useful for setting new target personalized therapy even in the treatment of endometrial cancer, moreover, endometrial cancer at low risk should be not underestimated for the incidence of relapse, and for this evaluation the molecular characterization may be useful. Moreover, these results suggest that the single analysis of primary tumors may be not sufficient for setting a specific personalized therapy targeted to avoid the relapse but may be necessary to join the molecular characterization of liquid biopsy to primary tissue.